ANTI-INFLAMMATORY EFFECT OF LIPID EXTRACT OF SEA PEN (VIRGULARIA GUSTAVIANA) IN MICE - Sharifi, Sharareh; Safaeian, Shila (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â Objective: Sea pens are a highly specialized group of anthozoa coelenterates. Sea pens were collected by wading at low tide in intertidal zone from Bandar Abbas Costal. Method: Sea pens were identified by classification keys, and samples were sending to the academic center of California for admission. Comparing identification keys genus from virgularidaes family was identified, it consisted of Virgularia gustaviana. To find an effective fraction, the inflammatory effect of lipid extract hexane of sea pen V. gustaviana was evaluated. In this study, lipid percentages of V. gustaviana were measured, and the percentage of sterol profile was assessed. To assess inflammation, mouse ear edema method was used. Male NMRI mice were categorized into three groups including positive control (dexamethasone 15 mg/kg), negative control (saline) and experimental one with dose of 10, 20, 40, and 60 mg/kg of lipid extracted of chloroform and hexane as a separate group. Results: Total lipid V. gustaviana was 21.96% and sterol profile which was 5680.31 mg/kg contains cholesterol 1910.38 mg/kg that equal 57.95% of total sterol and brassicasterol, campesterol, campestanol, stigmasterol, beta-sitosterol were measured. Fatty acid profile was measured by gas chromatography-mass and heptadecane 44.25%, beta.-Bisabolene ss Cyclohexene’1, 18.16%, and methyl arachidonate 54.17% was assessed. Statistical analysis was performed that anti-inflammatory effect of all doses of 40-10 mg/kg is significant to the control. Conclusion: Chloroform and hexane extracts of sea pen has a strong anti-inflammatory effects even at low doses which is probably due to 54% arachidonic acid in the compounds. Keywords: Anti-inflammatory activities, Lipid extract, Sea pen (Virgularia gustaviana).